MAPEAMENTO DAS CONDIÇÕES DE TRABALHO DOS JORNALISTAS DE CAMPO GRANDE-MS: Análise dos jornais on-line Midiamax e Campo Grande News - Eduardo Rafael Fregatto (2024)
The purpose of this dissertation is to map the working conditions and precariousness of online journalism in Campo Grande, Mato Grosso do Sul. In developing the theoretical framework, we provide an overview of the crisis in the journalism business model, technological transitions, and the flexibilization of labor relations. These elements have intensified the process of precariousness, adversely affecting the quality of news and the health of professionals. We also address the credibility crisis faced by journalism, the violence suffered by professionals in the field, and the difficulties encountered in newsrooms during the Covid-19 pandemic. Next, we highlight the geographic and territorial perspective of work, considering that journalism produced in Campo GrandeMS is distant from the country's media-concentrated region and displays several characteristics attributed to regional journalism. The objective is to map, through a case study, the main expressions of precarious work in online journalism portals in the capital of Mato Grosso do Sul. In the empirical phase, we conducted in-depth interviews with ten journalists from the Campo Grande News and Midiamax portals. The results were analyzed using descriptive and, at times, comparative strategies. The analyses reveal that, despite having formal employment contracts and guaranteed labor rights, professionals from Campo Grande describe a tiring routine, with reports of moral harassment and impacts on their health. The characteristics present in regional journalism influence the expressions of precariousness. Some journalists remain optimistic about the essential role of journalism, although most consider changing careers.